COMPARATIVE ANALYSIS OF CIRCUMFERENTIAL RESECTION MARGIN CONDITION DURING THE LAPAROSCOPIC AND OPEN TOTAL MESORECTAL EXCISION - Azimov, E.H. (World of Medicine and Biology, 2022)
The research work was carried out under the examination and treatment of 103 patients diagnosed with rectal carcinoma. The patients were divided into 2 semi-groups: 47 patients implemented total mesorectal excision in a laparoscopic way; 56 patients implemented total mesorectal excision in an open way. MRT examination of the small pelvis, CT examination of the chest cavity and abdominal cavity, colonoscopy, appointment of the oncomarkers in blood and other methods of examination were used in the course of the research. The factors like the tumor size, invasion depth, metastatic damage of the mesorectal lymph nodes, tumor emboles, tumor deposits, distance from the anus, phase of the tumor process and quality of the total mesorectal excision have statistical exact effect on the circumferential resection margin status during the pathohistological examination of the drug made. The circumferential resection margin was positive in T3/T4 masses in 66.7 % cases, in the patients with their lymph nodes damaged metastatically in 57.1 % cases, in the tumors of III phase in 57.1 % cases, in large tumors more than 4cm in 50 % cases. 33.3 % local recurrence was noted in these patients (p
Keywords: Rectal carcinoma; circumferential resection margin; total mesorectal excision; tumor embolus; tumor deposits; metastatic lymph nodes